Yiddish or not? Holocaust remembrance, commemorative ceremonies, and questions of language among Parisian Jews, 1944–1967. Issue 2 (3rd April 2021) - Perego, Simon
ABSTRACT: Between 1945 and the late 1960s, a large number of Yiddish-speaking Jews lived in Paris where most of them had settled before World War II. In the aftermath of the war, Parisian Yiddish culture – as everywhere else – was deeply marked by the Holocaust and destruction of Yiddish life in Eastern Europe. As the Yiddish dimension of Holocaust memory has mainly been studied through the prism of literature, testimony, and historiography, this essay aims to explore the place accorded to Yiddish in Parisian Jewish commemorations, defined as ceremonies involving different categories of actors, and offering a narrative of the past through speeches, specific places, and rituals. To address this subject, I analyze first the commemorative functions attributed to the Yiddish language, as well as the ways in which it was used to collectively remember the catastrophe. Second, I study the conflicts launched by commemorative uses of Yiddish between Jewish subgroups and between generations. By doing so, my paper intends to consider Yiddish culture after 1945 as a fundamental, but also polemical, element in the production of commemorative practices among Parisian Jews during the two decades following the Liberation.